Technology readiness and economic benefits of swappable battery standard: Its implication for open innovation - Era Febriana Aqidawati; Wahyudi Sutopo; Eko Pujiyanto; Muhammad Hisjam; Fakhrina Fahma; Azanizawati Ma'aram (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The innovation of electric motorcycle swap-battery (EMSB) technology encourages the formation of a new ecosystem at the early stage of the supply chain. The EMSB technology has allowed an open innovation system with collaboration between supply-chain players, universities, and the government for finding a thriving solution to enable the faster adoption and diffusion of EMSB in Indonesia. Standardization is seen as a way to accelerate the downstream EMSB technology innovation to leverage the economic benefits and to support the growth of a green economy in Indonesia. This study aimed to propose a model with which to measure the technology readiness of the EMSB's stakeholders in implementing the swappable battery (SB) standard. We developed the technometric framework and Economic Benefits of Standards-ISO Methodology 2.0. We generated 13 criteria of technoware, humanware, inforware, and orgaware and 21 indicators of the standard's impacts to be utilized as a measurement model. We interviewed 11 respondents consisting of the standard regulator, research and development center, manufacturer, testing labs, and product-certification bodies. The results show the technology contribution coefficient (TCC) and earnings before interest and taxes (EBIT) value representing the SB standard's feasibility. The proposed model can evaluate the weak points and propose strategies to leverage the SB standard's technology readiness and economic benefits.
Keywords: 650; economic benefits; electric motorcycle swap-battery; green economy; open innovation; swappable battery standard; technology readiness